Pengaruh Kontrol Rutin terhadap Kesembuhan pada Penderita Tuberkulosisi Paru di Puskesmas Lontar Kecamatan Sambikerep Kota Surabaya - Athalia N. Vionita; Muzaijadah Retno Arimbi; Mira Kusuma Wardhani (Calvaria Medical Journal, 2024)
Introduction: Globally, tuberculosis is among the 10 biggest killer diseases. There were 10 million cases of tuberculosis in 2018, with 1.5 million deaths caused by the disease. Objective: This study aims to determine whether there is an effect of routine control on recovery in Pulmonary Tuberculosis patients at the Lontar Health Center, Sambikerep District, Surabaya City. Method: The nominal quantitative research method was used in this research. The research method used is the cross-sectional survey method, namely data collection is carried out retrospectively through observation of medical records to provide an overview of the treatment of Tuberculosis (TB) patients and evaluation of the results of the treatment. Results: Based on the results of the Spearman Rank test obtained from the SPSS 20.0 for Windows computer program, the p-value obtained is p = 0.00 which indicates that there is a relationship between routine control and recovery in pulmonary tuberculosis patients. The results of the correlation coefficient show that the recovery of pulmonary TB patients is not only influenced by their compliance in routine check-ups at the health center, but also by various other supporting factors. Conclusion: Patients who undergo regular routine check-ups show a higher rate of recovery compared to patients who do not undergo check-ups consistently. This shows the importance of regular monitoring in supporting patient compliance with treatment and minimizing the risk of drug resistance.